A classification of fitness components in elite alpine skiers: A cluster analysis - Penitente, G.; Young, H. A.; Sands, W. A.; McNeal, J. R. (International Journal of Environmental Research and Public Health, 2024)
The current study is an exploratory, secondary data analysis of a selection of physiological and biomechanical fitness components used to assess elite alpine skiers. The present study will provide new knowledge that can be used to aid training prescription and talent identification. A hierarchical cluster analysis was used to identify groups of variables that are crucial for elite alpine skiers and differences based on sex and competition level. The key findings of the study are the patterns that emerged in the generated dendrograms. Physiological and biomechanical fitness components are differentiated in the dendrograms of male and female world-cup-level alpine skiers, but not in non-world-cup athletes. Components related to the aerobic and anaerobic capacity tightly cluster in male athletes at world cup and non-world-cup level, and female world cup athletes. Lower body explosive force production appears to be more critical in male world cup athletes than female world cup athletes. More research is needed into the importance of isometric strength in the lower body. Future research should use larger sample sizes and consider other alpine ski demographics.